Colorectal Cancer in Young Age Group: Where Do We Stand? - Rawal, Sushil Bahadur; Laudari, U.; Thapa, A.; Jha, M.K.; Shrestha, D.B.; Maharjan, M.; Rayamajhi, J.; Malla, S. (Nepal Medical College Journal, 2019)
Colorectal cancers in young are in increasing trend. Young patients tend to ignore symptoms and present at advanced stage due to aggressive tumour biology, and also due to traditional dictum of routine screening after >50 years these groups of patients are given less priority. The objective of our study was to estimate the burden of problem among young population and increase awareness among medical personnel and general population of early detection for disease. We conducted retrospective cross sectional study using whole sampling method among patients operated by single gastrointestinal surgery unit. Demographic details, malignancy information, surgical procedure and histopathological examination were studied. All cases admitted as colorectal cancer from 2013 to 2017 at gastrointestinal surgery unit of Shree Birendra Hospital were included. The collected data were entered in SPSS version 16 and analyzed. Likelihood of occurrence of adenocarcinoma was studied using logistic regression model. Among total 104 cases operated, only 99 cases were having complete data with median age: 55 years. Thirty seven percent of the individuals having colorectal malignancies were younger than 50 years. Rectum was the commonest site (52, 52.5%) for occurrence of colorectal malignancy. Males were 1.493 (0.402-5.545) times more likely to have colorectal adenocarcinoma than females. Young age (<50 years) was associated with an increased likelihood of colorectal adenocarcinoma {OR=1.771(0.443-7.233)} than older people. Colorectal cancer in young age is in increasing trends. Increasing awareness among medical personnel and general population is must for early detection.